LOCAL WISDOM AS ALTERNATIVE OF DISASTER COMMUNICATION MANAGEMENT IN MOUNT SINABUNG, KARO REGENCY, NORTH SUMATERA, INDONESIA - Puji Lestari; Eko Teguh Paripurno (Department of Communication Studies, Faculty of Social and Political Sciences Universitas, 2015)
This research has objective to describe local wisdom as alternative of disaster communication management in Mount Sinabung in Karo regency, North Sumaera. This research used descriptive qualitative method. And for data collection, it used; interview, focus group discussion (FGD), observation, dan documentation. The subject of this research was the people of Sinabung disaster, Local government of Karo, local leader, NGO, reporters, and etc. It used purposive and snowball sampling as the research sample. This research has finding that the people of Sinabung has some implemented local wisdom: 1). Local wisdom such as Karo language; (2) Jambur; (3) Philosophy, (4) Ecology; (5) Family system; (6) Work year. The result of this research recommended; (1) the government needs to raise the understanding, conscience, careness, and the people participation to use Karo language wisely and ethically, (2) Karo people must keep the philosophy, (3) People are obligated to care with their environment, and keep the clarity and purity of Mount SInabung, and (4) Government must provide them the law through making the village rules related to the usage of Jambur as refuge, (5) People must maintain the work year ethic and family system that support the communication of Sinabung disaster.